A propósito del servicio militar voluntario peruano: Una revisión de los últimos debates que abordan el ejercicio constitucional en el Perú contemporáneo - Morales Tinta, Stefany (2022)
With the arrival of the pandemic due to Covid-19, the worsening of citizen insecurity and the rise of the new government, the nature of voluntary military service has been debated, seeking to make it part of a public policy that addresses young people. Against this background, at the social level some debates have been developed that point out before the importance of understanding the structural bases of youth. Starting from this approach, the following paper presents a review that shows the trajectory and scope of the exercise of voluntary military service in contemporary Peru. The structure of the text is based on two thematic axes: studies and approaches to military service and military service in the political agendas of governments. Interest in the exercise of military service in Latin America and its variants is part of a large body of research and there is a varied literature on the historical notion of military service. However, only in some cases have social aspects been considered in a very superficial way and not directly related to military service, but with respect to the profession. Given this absence, it is hoped to contribute with a scope that highlights this often invisible and complex space, considering that it can be promising in terms of data for the analysis of political decisions that lead to strengthening the actions of the Armed Forces institutions by time to convene volunteer military personnel and future public policies for youth.